Exploring The Utilization of Traditional Vietnamese Cultural Elements in Advertising (International Journal of Scientific Research in Science and Technology, 2024)
This study aimed to explore traditional Vietnamese cultural elements used in advertising by analyzing 82 advertisements from four major Vietnamese beer companies. The cultural elements were classified into four main groups: ideology, customs, religion and art. The results of the study showed that the use of traditional cultural elements in advertising can help increase customer interest, helping to spread the brand effectively. In addition, the study also pointed out the potential risks associated with superficial or inappropriate use of cultural elements that can lead to cultural distaste and damage the brand. The study emphasized that the careful and creative use of cultural elements can help maintain brand strength and spread the culture of the country.
Keywords: Vietnam; Traditional Culture; Advertising; Cultural Elements; Brand Resonance